Reducing systematic errors in time-frequency resolved mode number analysis. (16th October 2015) - Horváth, L; Poloskei, P Zs; Papp, G; Maraschek, M; Schuhbeck, K H; Pokol, G I
Abstract: The present paper describes the effect of magnetic pick-up coil transfer functions on mode number analysis in magnetically confined fusion plasmas. Magnetic probes mounted inside the vacuum chamber are widely used to characterize the mode structure of magnetohydrodynamic modes, as, due to their relative simplicity and compact nature, several coils can be distributed over the vessel. Phase differences between the transfer functions of different magnetic pick-up coils lead to systematic errors in time- and frequency resolved mode number analysis. This paper presents the first in situ, end-to-end calibration of a magnetic pick-up coil system which was carried out by using an in-vessel driving coil on ASDEX Upgrade. The effect of the phase differences in the pick-up coil transfer functions is most significant in the 50–250 kHz frequency range, where the relative phase shift between the different probes can be up to 1 radian (∼60°). By applying a correction based on the transfer functions we found smaller residuals of mode number fitting in the considered discharges. In most cases an order of magnitude improvement was observed in the residuals of the mode number fits, which could open the way to investigate weaker electromagnetic oscillations with even high mode numbers.